2021
DOI: 10.1007/s10708-021-10487-2
|View full text |Cite
|
Sign up to set email alerts
|

A socio-geographic perspective of health and economic impacts of COVID-19 on poor households in ghana

Abstract: COVID-19 outbreak has had multidimensional effects on human lives. The impacts are expected to be more severe on poor households, especially in resource-constraint economies such as Ghana. The Country has a higher poverty rate [24.2%] and this is likely to upsurge in the coming years due to this pandemic. We aimed to document the pandemic-related health and socioeconomic hazards in Ghana. A content analysis of relevant literature, and a qualitative survey using a socioecological lens were conducted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This study focused on rural older adults due to the exacerbated challenges they face in accessing health services compared with their urban counterparts (Asante et al, 2021; Bocker et al, 2012; Crabb & Hunsley, 2006; Dempsey et al, 2003; Eckert et al, 2004; Gyasi, Phillips, & Adam, 2020). Rural older Ghanaians are more likely to report transportation challenges, financial constraints and longer travel distances to accessing needed health services (Agyemang‐Duah et al, 2019).…”
Section: Ghana Context For Rural Older Adultsmentioning
confidence: 99%
“…This study focused on rural older adults due to the exacerbated challenges they face in accessing health services compared with their urban counterparts (Asante et al, 2021; Bocker et al, 2012; Crabb & Hunsley, 2006; Dempsey et al, 2003; Eckert et al, 2004; Gyasi, Phillips, & Adam, 2020). Rural older Ghanaians are more likely to report transportation challenges, financial constraints and longer travel distances to accessing needed health services (Agyemang‐Duah et al, 2019).…”
Section: Ghana Context For Rural Older Adultsmentioning
confidence: 99%
“…The Ministry of Health, through the Ghana Health Service, also issued guidelines for isolation, among other things, on March 19, 2020, which mandated close contact of infected people to self-isolate for a minimum of 14 days [16]. There was a ban on all social gatherings, including schools, workshops, religious gatherings, and conferences, to limit the spread of the virus [23,40]. Private burials were allowed with a limited number of 25 people in attendance.…”
Section: Policy Initiatives After the Confirmation Of Covid-19 Cases ...mentioning
confidence: 99%
“…Ghana, like many developing countries, has inequitable healthcare delivery systems in which many people in the far-to-reach communities cannot access quality healthcare [8,40,43]. The massive infrastructure deficit in the healthcare delivery system in Ghana was of great concern when the outbreak was announced by WHO [8,36].…”
Section: Policy Initiatives After the Confirmation Of Covid-19 Cases ...mentioning
confidence: 99%
“…Other studies reported that the partial lockdown in the Accra and Tema metropolis and the greater Kumasi area, which have the highest concentration of population in Ghana and were the epicentre of infection [3,30], resulted in hardships for the informal economy and the urban-slum [3]. Some of the effects were loss of jobs, income and lack of food, increase in poverty levels and fear of accessing health care [31][32][33][34]. This current study contributes to literature by employing a concurrent triangulation mixed methods design, to examine the socio-economic and health effects of COVID-19 as well as the categories of vulnerable individuals (urban-slum and rural residents) that are more susceptible to the effects of COVID-19 in Ghana.…”
Section: Introductionmentioning
confidence: 99%